16‐year simulation of Arctic black carbon: Transport, source contribution, and sensitivity analysis on deposition. Issue 2 (19th January 2013) - Sharma, S.; Ishizawa, M.; Chan, D.; Lavoué, D.; Andrews, E.; Eleftheriadis, K.; Maksyutov, S.
Abstract : [1] Arctic regional climate is influenced by the radiative impact of aerosol black carbon (BC) both in the atmosphere and deposited on the snow and ice covered surfaces. The NIES (National Institute for Environmental Studies) global atmospheric transport model was used, with BC emissions from mid‐latitude fossil fuel and biomass burning source regions, to simulate BC concentrations with 16 year period. The model‐simulated BC agreed well with the BC observations, including the trends and seasonality, at three Arctic sites: Alert (Nunavut, Canada), Barrow (Alaska, USA), and Zepplin, Ny‐Ålesund (Svalbard, Norway). The equivalent black carbon (EBC, absorption inferred BC) observations at the three Arctic locations showed an overall decline of 40% from 1990 to 2009; with most change occurring during early 1990s. Model simulations confirmed declining influence on near surface BC contribution by 70%, and atmospheric BC burden by one half from the Former Soviet Union (FSU) BC source region over 16 years. In contrast, the BC contribution from the East Asia (EA) region has little influence at the surface but atmospheric Arctic BC burden increased by 3 folds. Modelled dry deposition is dominant in the Arctic during wintertime, while wet deposition prevails at all latitudes during summer. Sensitivity analyses on the dry and wet deposition schemes indicate that parameterizations need to be refined to improve on the model performance. There are limitations in the model due to simplified parameterizations and remaining model uncertainties, which requires further exploration of source region contributions, especially from growing EA source region to Arctic BC levels in the future is warranted. Key Points: Black carbon trends in the Arctic surface have declined by 40% since 1990 FSU influence on Arctic BC declined while EA increased aloft over 16 years Biomass burning contributes one third to the Arctic atmospheric BC burden